Analisis Ketidakmerataan Layanan Publik Money Remitance Western Union di Kantor Pos Kota Tanjungpinang Terhadap Geraknya Modernisasi Layanan Bank Umum - Giniung Pardita; Anugrah Satriadi; Denny Andrias (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
Western Union is a global financial service company renowned for its money transfer services. With thousands of locations worldwide, including post offices and banks, Western Union enables individuals to send and receive money quickly and securely to nearly any country in the world. The main advantages of using Western Union include speed, convenience, and accessibility. In many cases, money transfers can be completed within minutes. Moreover, with the vast number of Western Union locations, the service is easily accessible to many people. However, it's crucial to be cautious of potential scams and always ensure that you're sending money to someone you know and trust. Additionally, the service fees of Western Union can be a consideration, depending on the amount of money sent and the destination country. Overall, Western Union is a solid choice for international money transfer needs, as long as it's used wisely and cautiously. This research shows that this lesser-known service can keep up with global transformation mobilization, introducing and fostering cooperation on service modernization. Using the literature study research method, this can include a study on overseas money transfer services.